Pulmonary Stereotactic Body Radiation Therapy of Oligometastatic Head-and-Neck Squamous Cell Carcinoma: A Multicenter Retrospective Study - Nägler, Franziska; Vorbach, Samuel; Mohamed, Ahmed Allam; Thaqi, Saranda; Adebahr, Sonja; Ehret, Felix; Kraft, Johannes; Fabian, Alexander; Weissmann, Thomas; Kaufmann, Justus; Drabke, Sophia; Looman, Esmée Lauren; et al. (International Journal of Radiation Oncology Biology Physics, 2025)
Purpose: The value of stereotactic body radiation therapy (SBRT) in patients with oligometastatic head-and-neck squamous cell carcinoma (HNSCC) remains unclear, as existing evidence is primarily derived from retrospective single-center analyses with small patient cohorts. This study aimed to evaluate the outcomes of pulmonary SBRT in patients with oligometastatic HNSCC and to identify factors associated with survival. Methods and Materials: This trinational multicenter cohort study, including 16 centers from Germany, Austria, and Switzerland, retrospectively analyzed patients with oligometastatic HNSCC undergoing SBRT for pulmonary metastases between 2010 and 2023. The primary outcome was overall survival (OS). Secondary outcomes included progression-free survival and incidence of local failures. Results: A total of 178 patients with 284 irradiated lung metastases were analyzed. The most common primary HNSCC subsites were oropharyngeal (n = 71), laryngeal (n = 37), and hypopharyngeal (n = 31). Lung metastases were treated with a median biologically effective dose (BEDα/β = 10 Gy) of 105 Gy (IQR, 84-113) at the planning target volume periphery. After a median follow-up of 40 months (95% CI, 34-46), the median OS and progression-free survival were 33 months (95% CI, 26-40) and 9 months (95% CI, 7-11), respectively. The 1-year cumulative incidence of local failures was 5.5% (95% CI, 3.2-8.8). One patient (0.6%) developed acute grade 3 dysphagia, and among 146 patients assessed for chronic toxicities, 2 (1.4%) experienced grade 3 events, with no grade 4-5 toxicities. On multivariable analysis, older (>65 years) patients (hazard ratio [HR], 1.59; 95% CI, 1.02-2.49; P = .040) and females (HR, 1.76; 95% CI, 1.04-2.99; P = .035) exhibited worse OS, whereas longer time between HNSCC diagnosis and first SBRT was associated with longer OS (HR, 0.99; 95% CI, 0.99-1.00; P = .045). Conclusion: SBRT for pulmonary metastases achieves excellent local control with minimal toxicity in patients with oligometastatic HNSCC. Prospective trials are needed to determine the optimal timing for integrating SBRT with systemic treatment.
CRIS-Team Scopus Importer:2025-02-14